FRI0227 The Burden of Axial Spondyloarthritis: A Comparison of the Radiographic and Non-Radiographic Groups. (9th June 2015) - Cetin, P.; Sen, G.; Capar, S.; Yarkan, H.; Kenar, G.; Sari, I.; Birlik, M.; Onen, F.; Akkoc, N.
Abstract : Background: Axial spondyloarthritis (axSpA) represents the whole clinical spectrum of ankylosing spondylitis (AS) including those at the non-radiographic (nr) stage of the disease. Although the disease burden associated with radiographic axSpA (classically known as AS) has been extensively studied, the burden associated with nr-axSpA is less well known. Objectives: To assess and compare the burden of radiographic and nr-axSpA Methods: This cross-sectional, observational study included consecutive AxSpA patients with varying disease severity, who attended our outpatient clinic between April 2014 and December 2014. During the visits, the following questionnaires were applied by trained health professionals:BASDAI, BASFI, HAQ-S, SF-36, ASQoL, Work Productivity and Activity Impairment (WPAI) and Work Productivity Survey (WPS). Results: A total of 381 AxSpA patients (279 AS) were analyzed. Nr-axSpA group, were younger (39.4 vs 43.1, p=0.007), more likely to be female (54% vs 33%, p<0.001), had a shorter disease duration (10.1 vs 16.0 years, p<0.001) and lower CRP (5.9 vs 13.2, p<0.001) and less common use of biologics (41.2% vs 26.5, p=0.008) despite higher BASDAI scores (Table ). Broadly similar results were found for the other clinical outcome measures. Of all the axSpA patients, 58% were employed, with non-manual (25%), mixed (19%) and manual works (14%). Only 1.1% of the patients could not work due to arthritis. Patients with nr-axSpA reported more work productivity loss at workplace and at home over the last month, but the difference was significant only for household activities. Subgroup analysis showed that this difference was only found in females. Conclusions: Patients with AS and nr-AxSpA demonstrate similar degree of disease burden and prodcutivity, with a greater impairment of household work in females. Low rate of inability to work due to arthritis in this population with a relatively high prevalence of anti-TNF use may be a reflection of the effectiveness of such therapies. Disclosure of Interest: None declared